FUNDAMENTALISME: SEMANGAT MENJAGA KEMURNIAN ISLAM KRITIK KONSTRUKTIF WILLIAM MONTGOMERY WATT - Muhammad Taufik (UIN Sunan Kalijaga Yogyakarta, 2015)
As a popular issue recently, the fundamentalism is more understood as a movement within a sect, school or religion that striving to return to what they believe as the fundamentals or the foundations. The groups followed this idea are often involved conflict with another groups even within their own religion for the reason that their missions are to get rid ofthe impurities ofreligion. In positive meaning,